Study on the regulatory role of MINK1 gene in the activation of NLRP3 inflammasome in common carp (Cyprinus carpio L.) - Liu, Rongrong; Zhao, Keying; Zhao, Yue; Yang, Guiwen; Li, Hua (Frontiers in Immunology, 2025)
The nucleotide oligomerization domain (NOD)-like receptor protein 3 (NLRP3) inflammasome is a cytosolic multiprotein complex that can be activated by a wide variety of stimuli. However, dysregulated activation of NLRP3 is implicated in the pathogenesis of chronic inflammatory diseases. Hence, the activity of NLRP3 is intricately governed by several regulatory mechanisms. Misshapen-like kinase 1 (MINK1), a serine/threonine kinase, plays an important role in the immune cell differentiation and inflammatory response regulation in mammals; however, its regulatory function in NLRP3 inflammasome activation in fish remains poorly understood. In the present study, a homolog gene of MINK1 (CcMINK1) was cloned and functionally characterized in common carp (Cyprinus carpio L.). The expression profiling disclosed that CcMINK1 was upregulated under spring viremia of carp virus (SVCV) and Aeromonas hydrophila stimulation. Overexpression of CcMINK1 promoted CcNLRP3-mediated inflammasome activation, including apoptosis-associated speck-like protein containing a CARD (ASC) oligomerization, speck formation, cysteine-requiring aspartate protease A/B (Caspase-A/B) enzyme activity and interleukin-1β (IL-1β) cleavage. Mechanistically, CcMINK1 interacted with CcNLRP3 via its S_TKC domain and facilitated CcNLRP3 phosphorylation, thereby promoting its aggregation and activation. Collectively, these discoveries unveil a novel regulatory mechanism that governs the functional regulation of CcNLRP3 and fine-tuning innate immune responses in teleost.